2020
DOI: 10.21203/rs.3.rs-30806/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extended spectrum beta-lactamase and fluoroquinolone resistance genes among Escherichia coli and Salmonella isolates from children with diarrhea, Burkina Faso.

Abstract: Background: The emergence and spread of multidrug-resistant gram-negative bacteria (MDR) has become a major public health concern worldwide. This resistance is caused by enzymes-mediated genes (i.e., extended spectrum beta-lactamases) that are common in certain Enterobacterioceae species. However, the distribution of these genes is poorly documented in Burkina Faso. This study aims to determine the prevalence and distribution of the resistant genes coding for broad spectrum beta-lactamases and quinolones in ru… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
1
4
2
Order By: Relevance
“…Our results showed 19.4% of SHV-type ESBLproducing E. coli which is a little similar to 21% detected in Pakistan [42]. By cons, this prevalence is higher than 0% [9] and 5.9% [17], previously reported in Burkina Faso but lower than 45% reported in Iran [27]. The bla CTX-M gene (Figure 4) has been detected in three E. coli isolates, while its prevalence was 25% in our earlier report [9] and 40.1% by a study conducted in Enterobacteriaceae from Burkinabe patients [17].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our results showed 19.4% of SHV-type ESBLproducing E. coli which is a little similar to 21% detected in Pakistan [42]. By cons, this prevalence is higher than 0% [9] and 5.9% [17], previously reported in Burkina Faso but lower than 45% reported in Iran [27]. The bla CTX-M gene (Figure 4) has been detected in three E. coli isolates, while its prevalence was 25% in our earlier report [9] and 40.1% by a study conducted in Enterobacteriaceae from Burkinabe patients [17].…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, OXA-type ESBL-producing DEC strains (38.7%) were the most frequently detected ESBL gene. This prevalence is lower than that reported in our previous study in rural area of Burkina Faso: 100% [9], also lower comparatively to 52% reported in Pakistan [42]. However, a recent study in young children reported 3% of commensal E. coli bearing the bla OXA gene in Bangladesh [41].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…S. enterica producing β-lactamases of OXA type have been reported in France (Le Hello et al, 2013) and Switzerland (Seiffert et al, 2014). Also recently it has been reported in Salmonella isolated from children with diarrhoea in Burkina Faso (Dembélé et al 2020).…”
Section: Discussionmentioning
confidence: 92%